Match performance and physiological capacity of male elite team handball players - Michalsik Bojsen, L.; Aagaard, P.; Madsen, K. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The present study demonstrated that modern male elite Team Handball (TH) comprises several types of movement categories, which during match-play place moderate-to-high d emands on intermittent endurance running capacity and where the anaerobic energy turnover may be very high in short periods of time. Signs of temporary fatigue and impaired physical performance were observed. Notably, physical demands differed substantially between playing positions.